2018
DOI: 10.1108/jhr-01-2018-028
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of foods among older people in northern communities of Thailand

Abstract: Purpose Due to the increasing population and diverse lifestyles of aging people in Thailand, close examination of their needs and health care problems is required. Availability and accessibility of food affects the health and well-being of aging people in the community; therefore, to enhance their quality of life, community nurses and health care personnel must understand the variety of foods in their diet, in order to provide suitable and culturally acceptable nutrition for the elderly. The purpose of this pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The traditional belief of consumption of local foods/products without chemicals from their own farms and integrating their folk practices with the health professionals’ advice and with the health information gained from past experiences were regularly performed for health promotion. Findings in another study (Bubpa & Nuntaboot, 2017) also suggested that older adults consumed local products to prevent and control noncommunicable diseases. In addition, like other studies conducted on the use of herbal medicine in Thailand (Peltzer & Pengpid, 2019; Sumngern et al, 2011), Thai local herbs were used by HOAs as health supplements and combined with modern medicines to improve their health.…”
Section: Discussionmentioning
confidence: 96%
“…The traditional belief of consumption of local foods/products without chemicals from their own farms and integrating their folk practices with the health professionals’ advice and with the health information gained from past experiences were regularly performed for health promotion. Findings in another study (Bubpa & Nuntaboot, 2017) also suggested that older adults consumed local products to prevent and control noncommunicable diseases. In addition, like other studies conducted on the use of herbal medicine in Thailand (Peltzer & Pengpid, 2019; Sumngern et al, 2011), Thai local herbs were used by HOAs as health supplements and combined with modern medicines to improve their health.…”
Section: Discussionmentioning
confidence: 96%
“…In regards to dietary behaviors, people in northern Thailand tend to favor eating sticky rice and oily noodles [11,12]. Moreover, for years, northern Thailand has had the largest proportion of people aged 60 years and over [13]. The majority of people work in agricultural sectors and have poor opportunities to access schools.…”
Section: Introductionmentioning
confidence: 99%
“…This model highlights the nexus between an individual's food choices and eating behaviors and their own previous experiences that they have had during important events in their lives (18,19). Moreover, this model highlights a series of influences, such as their individual health (9,19), their interpersonal relationships in society (20,21), their food environment (22), and the economic system they live under (23). A combination of experiences and influences creates an individual's food choice values.…”
Section: Theoretical Frameworkmentioning
confidence: 99%